Use of the Ilizarov method to manage a septic tibial fracture nonunion with a large cortical defect - Owen, M.A (Journal of small animal practice, 2000)
The use of a ‘hybridised’ llizarov ring fixator is described in the salvage of a septic nonunion of a comminuted tibial fracture with a large diaphyseal cortical sequestrum in an 11‐month‐old German shepherd dog. A ring fixator assembly incorporating half pin application was chosen to provide flexibility of fixation placement options in limited bonestock which had previously been subject to conventional Kirschner‐Ehmer external fixation. Diaphyseal regeneration was achieved by stimulating bone trophism through the axial loading properties of the Ilizarov fixator and the biological osteoinductive properties of cancellous bone autograft. The young age of the dog was considered to make it an optimal candidate for salvage in spite of its highly excitable temperament. Fully functional fracture union with resolution of osteomyelitis was achieved at eight weeks following revision without recourse to intercalary transportation or cortical grafting. Problems with postoperative management of the dog resulted in minor complications and mechanical failure of some of the frame components.